Characterization of Meteorological Drought Using Standardized Precipitation Index and Standardized Precipitation Evapotranspiration Index Methods in North Sumatera - Fanly Parhimpunan Manullang; Kerista Tarigan; Marhaposan Situmorang; Syahrul Humaidi; Deassy Eirene Diana Doloksaribu; Yahya Darmawan (IKIP Mataram, 2023)
Climate variability in Indonesia is influenced by several global factors including El Niño Southern Oscillation and Indian Ocean Dipole, one consequence of climate variability is drought. The drought index is used to identify and describe the level of drought in an area, the methods used in this study are the Standardized Precipitation Index and the Standardized Precipitation Evapotranspiration Index which are calculated based on climate data with a span of 24 years as many as 67 rain observation posts in North Sumatra using R Studio software. The purpose of this study is to determine the factors of global climate phenomena that affect drought in North Sumatra and its impact on rice crop productivity and analyze drought characteristics spatially and temporarily. The resulting index values are then analyzed using correlation methods to see their relationship with ENSO and IOD. The results showed that the incidence of the ENSO phenomenon had a very strong relationship with meteorological drought in North Sumatra with a correlation value range of -0.85 to -0.97, and as many as 62.5% of 32 districts experienced a decrease in rice crop productivity during El Niño with strong intensity in 2015.